The rheumatological examination. (February 2022) - Batten, Rebecca; Coady, David
Abstract: Musculoskeletal disorders are the most common cause of disability in the UK. They are associated with significant morbidity and polypharmacy, particularly in an ageing population with multiple co-morbidities. Two programmes of examination that have been developed are a screening assessment (Gait, Arms, Legs, Spine (GALS)) and a more in-depth Regional Examination of the Musculoskeletal System (REMS). These programmes provide a structured assessment, which enables competent and confident examination skills, ensuring an accurate diagnosis.